Методы определения составляющих полной мощности в системах электрической тяги - Костин, Н.А.; Петров, А.В. (Технічна електродинаміка, 2011)
Ways of definition of components of total power in systems of electric propulsion are stated. Using the method of correlation functions, the new approach to determination of these constituents is offered. The numeral calculations of active, inactive and total power are executed, and also coefficient of inactive power has been calculated by three methods. The estimation of relation of non-productive losses of active electric power to the reactive power conditioned flowing in a hauling network, to consumed is resulted also. It is set that this index can exceed 10%.